2022
DOI: 10.1111/ene.15353
|View full text |Cite
|
Sign up to set email alerts
|

Acute onset movement disorders in diabetes mellitus: A clinical series of 59 patients

Abstract: Background and purpose No previous study has assessed the frequency and clinical–radiological characteristics of patients with diabetes mellitus (DM) and acute onset nonchoreic and nonballistic movements. We conducted a prospective study to investigate the spectrum of acute onset movement disorders in DM. Methods We recruited all the patients with acute onset movement disorders and hyperglycemia who attended the wards of three hospitals in West Bengal, India from August 2014 to July 2021. Results Among the 59 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 30 publications
(134 reference statements)
1
19
0
Order By: Relevance
“…Among them, small vessel disease was characterized by obliteration of small artery lumen, strikingly thickening of all three layers of the wall, hyaline change, and remarkable proliferation of small blood vessels, which were similar to diabetic retinopathy. In this study, patient 2 had diabetic retinopathy and diabetic nephropathy, combined with previous studies [ 18 , 28 ], showed that there was correlation between striatal lesions and microangiopathy. ⑵ Infection and autoimmune inflammatory response theory.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Among them, small vessel disease was characterized by obliteration of small artery lumen, strikingly thickening of all three layers of the wall, hyaline change, and remarkable proliferation of small blood vessels, which were similar to diabetic retinopathy. In this study, patient 2 had diabetic retinopathy and diabetic nephropathy, combined with previous studies [ 18 , 28 ], showed that there was correlation between striatal lesions and microangiopathy. ⑵ Infection and autoimmune inflammatory response theory.…”
Section: Discussionsupporting
confidence: 73%
“…Non-ketotic hyperglycemia, unilateral limb choreographic dyskinesia, and striatal abnormalities on neuroimaging are typical signs of DS. Previous studies have found that chorea associated with hyperglycemia occurs mostly unilaterally and rarely bilaterally; a few may occur in hypoglycemic states or after correction of hyperglycemia [ 1 , 16 18 ], and a few DS cases reported no chorea [ 18 20 ] or had nonchoreic and nonballistic movements [ 7 , 12 , 14 , 18 , 21 , 22 ]. The imaging manifestation may also be unremarkable [ 16 , 18 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Diabetic striatopathy (DS) is a rare complication secondary to hyperglycemia, featured by the choreiform movements, and reversible striatal abnormalities in neuroimaging (Chua et al, 2020 ). In recent years, an increasing number of studies have described the clinical characteristics of DS (Kim et al, 2015 ; Yu et al, 2017 ; Wang et al, 2020 ; Zheng et al, 2020 ; Zhao et al, 2021 ; Dubey et al, 2022 ; Tsalta-Mladenov et al, 2022 ). However, the simultaneous occurrence of DS and acute ischemic stroke (AIS) in the striatum has not been reported.…”
Section: Introductionmentioning
confidence: 99%